2020
DOI: 10.1097/dcr.0000000000001658
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Lung Cancer Inflammation Index Predicts Outcomes of Patients With Colorectal Cancer After Surgical Resection

Abstract: BACKGROUND: The advanced lung cancer inflammation index is considered a useful prognostic biomarker of clinical outcomes in patients with malignancies. However, the prognostic value of the advanced lung cancer index in patients with colorectal cancer who underwent surgical resection remains unclear. OBJECTIVE: In this study, we evaluated the prognostic value of the advanced lung cancer index in patients with colorectal cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…ALI was originally used to assess the prognosis of lung cancer patients, such as non-small cell lung cancer 28 and small cell lung cancer. 29 Soon after, researchers found that ALI is also a good independent prognostic indicator in nasopharyngeal carcinoma, 30 head and neck squamous cell carcinoma, 31 32 esophageal cancer, 32 gastric cancer, 21,33 colorectal cancer, 34,35 melanoma, 36 and diffuse large B-cell lymphoma. 37 ALI is an index related to inflammation and nutritional status.…”
mentioning
confidence: 99%
“…ALI was originally used to assess the prognosis of lung cancer patients, such as non-small cell lung cancer 28 and small cell lung cancer. 29 Soon after, researchers found that ALI is also a good independent prognostic indicator in nasopharyngeal carcinoma, 30 head and neck squamous cell carcinoma, 31 32 esophageal cancer, 32 gastric cancer, 21,33 colorectal cancer, 34,35 melanoma, 36 and diffuse large B-cell lymphoma. 37 ALI is an index related to inflammation and nutritional status.…”
mentioning
confidence: 99%
“…The novel inflammation-related marker ALI was first evaluated as a powerful prognostic index for metastatic non-small cell lung cancer. 11 The ALI combines BMI, ALB, and NLR (BMI × ALB/NLR), all of which play pivotal roles in nutritional, immune, and systemic inflammation 12,30 Previous studies have reported that the ALI is associated with non-small cell lung cancer, 11 esophageal squamous carcinoma, 17 colorectal cancer, 15 and diffuse large B-cell lymphoma. 16 A low ALI based on a decreased BMI, lower ALB, and/or high NLR indicates a high level of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several studies have also reported associations between low ALI and clinical outcomes in patients with a variety of malignancies. 11,[15][16][17] However, to our knowledge, no study has assessed the diagnostic utility of the ALI for CAD or CAC.…”
Section: Introductionmentioning
confidence: 99%
“…ALI was calculated as BMI (kg/m 2 ) ×ALB (g/dL) ÷ NLR. 8 Preoperative serum carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC), cytokeratin-19 fragment (CYFRA 21-1), and neuron-specific enolase (NSE) levels were measured by enzyme immunoassays at the same hospital laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The prognostic accuracy of ALI has been tested in patients with different malignancies including lung cancer. 7 9 Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. 10 However, the prognostic significance of ALI has not been adequately investigated in patients with NSCLC following video-assisted thoracic surgery (VATS) as the resection technique, especially patients at stage III.…”
Section: Introductionmentioning
confidence: 99%